An Orchestra of Words in the Storm of Politics: a Linguistic Analysis of the Regent of Pati’s Utterances in the Regional Tax Crisis - Mohammad Fikri; Ashraf Abdelbaky (At Taawun Bangun Bangsa, 2025)
The 2025 PBB-P2 tax controversy in Pati Regency offers a revealing case of how political discourse functions as both a communicative tool and a strategic instrument during governance crises. This study analyzes three public statements by the Regent—drawn from verified news sources and recordings—using a qualitative critical discourse analysis informed by Searle’s speech act theory and Wodak’s discourse-historical approach. The analysis identifies a rhetorical trajectory from direct confrontation, marked by imperatives and declaratives asserting political strength, through a mitigation phase framed as denial of intent, to a procedural defense invoking constitutional legitimacy. These shifts are contextualized within Javanese politeness norms and the dynamics of digital media amplification. The Regent’s confrontational style clashed with cultural expectations of indirectness, intensifying public backlash, while the apology’s self-justificatory tone limited its restorative effect. The final procedural framing reasserted formal authority but failed to address emotional grievances, particularly in online spaces shaped by the viral initial statement. By linking linguistic strategies to socio-cultural and technological contexts, the study contributes to discourse studies and offers insights for culturally responsive crisis communication in democratic governance.